Diagnosis of periprosthetic hip infection: a clinical update - Luppi, Valentina; Regis, Dario; Sandri, Andrea; Magnan, Bruno (Acta Biomedica Atenei Parmensis, 2023)
Periprosthetic joint infection (PJI) is a serious complication following hip arthroplasty, which is associated with significant health cost, morbidity and mortality. There is currently no consensus in the optimal definition of PJI, and establishing diagnosis is challenging because of conflicting guidelines, numerous tests, and limited evidence, with no single test providing a sensitivity and specificity of 100%. Consequently, the diagnosis of PJI is based on a combination of clinical data, laboratory results from peripheral blood and synovial fluid, microbiological culture, histological evaluation of periprosthetic tissue, radiological investigations, and intraoperative findings. Usually, a sinus tract communicating with the prosthesis and two positive cultures for the same pathogen were regarded as major criteria for the diagnosis, but, in recent years, the availability of new serum and synovial biomarkers as well as molecular methods have shown encouraging results. Culture-negative PJI occurs in 5-12% of cases and is caused by low-grade infection as well as by previous or concomitant antibiotic therapy. Unfortunately, delay in diagnosis of PJI is associated with poorer outcomes. In this article, the current knowledge in epidemiology, pathogenesis, classification, and diagnosis of prosthetic hip infections is reviewed.